Effect of different concentrations of fluoride varnish on enamel surface microhardness: An in vitro randomized controlled study - Priya Subramaniam; Sangeeta Telegeti (Wolters Kluwer Medknow Publications, 2016)
Introduction: Dental caries occurs as a result of demineralization-remineralization phases occurring alternately at the tooth surface. Fluoride varnishes have a caries-inhibiting effect on teeth through remineralization. The resulting enamel is resistant to acid dissolution. Aim: The aim of this study is to assess enamel surface microhardness (SMH) following varnish application with different fluoride concentrations. Materials and Methods: Ninety freshly extracted, caries-free premolar teeth were used. Teeth were sectioned to obtain enamel blocks from the buccal surface of crown. The blocks were serially polished and flattened, embedded in acrylic blocks and smoothened to achieve a flat surface. The samples were divided into three groups, namely, A, B, and C consisting of 30 enamel blocks each. In Group A, Fluor Protector® varnish and in Group B, Bi-Fluorid 10® varnish was applied. Group C served as controls. All samples were subjected to a demineralization-remineralization cycle for 7 days. The SMH of enamel was measured. Data obtained was subjected to statistical analysis using the Student's t-test and one-way ANOVA. Results: The mean values of enamel SMH of Groups A and B were 496.99 ± 4.81 and 449.47 ± 7.37 Vickers Hardness Number, respectively. Conclusion: Fluor Protector varnish showed significantly higher enamel SMH than that of the other two groups (P < 0.05).